Invasive management of acute coronary syndrome: Interaction with competing risks. (15th October 2018) - Chuang, Anthony (Ming-yu); Hancock, David G.; Halabi, Amera; Horsfall, Matthew; Vaile, Julian; De Pasquale, Carmine; Sinhal, Ajay; Jones, Dylan; Brogan, Richard; Chew, Derek P.
Abstract: Background: The aim of this study was to characterise the interaction between ACS- and non-ACS-risk on the benefits of invasive management in patients presenting with acute coronary syndrome (ACS). Methods: Consecutive patients admitted to a tertiary hospital's Cardiac Care Unit in the months of July–December, 2003–2011 with troponin elevation (>30 ng/L) were included. "ACS-specific-risk" was estimated using the GRACE score and "non-ACS-risk" was estimated using the Charlson-Comorbidity-Index (CCI). Inverse-probability-of-treatment weighting was used to adjust for baseline differences between patients who did or did not receive invasive management. A multivariable flexible parametric model was used to characterise the time-varying hazard. Results: In total, 3057 patients were included with a median follow-up of 9.0 years. Based on CCI, 1783 patients were classified as 'low-non-ACS risk' (CCI ≤ 1; invasive management 81%; 12-month mortality 5%), 820 as 'medium-non-ACS risk' (CCI 2–3; invasive management 68%; 12-month mortality 13%), and 468 as 'high-non-ACS risk' (CCI ≥ 4; invasive management 47%; 12-month mortality 29%). After adjustment, invasive management was associated with a significant reduction in one-year overall-mortality in the 'low-risk' and 'medium-risk' groups (HR = 0.38, 95%CI:0.26–0.56; HR = 0.46, 95%CI:0.32–0.67); but not in the 'high-risk' group (HR = 1.02, 95%CI:0.67–1.56). The absolute benefit of invasive management was greatest with higher baseline ACS-risk, with a non-linear interaction between ACS- and non-ACS-risk. Conclusions: There is a complex interaction between ACS- and non-ACS-risk on the benefit of invasive management. These results highlight the need to develop robust methods to objectively quantify risk attributable to non-ACS comorbidities in order to make informed decisions regarding the use of invasive management in individuals with numerous comorbidities. Highlights: Benefits of invasive management for ACS not clear if significant comorbidities ACS risk and non-ACS risk on benefits of invasive management evaluated Invasive management beneficial if low and medium non-ACS risk, but not if high Benefit diminished over time and modified by non-linear interaction with ACS risk Tools to robustly model non-ACS risk to guide treatment decision needed